STUDIES OF RADIATION PASTEURISATION OF MEDIUM FATTY FISH I. CONTROL OF RADIATION INDUCED OXIDATIVE CHANGES IN WHITE POMFRET (Stromateus cinereus) BY VACUUM PACKAGING - KAMAT, S V; KUMTA, U S (Fishery Technology, 2025)
Marked differences were observed in proximate biochemicalcompositions of the skin and muscle of white pomfret. The skinshowed comparatively higher content of extractable lipids and was:more susceptible to radiation-induced oxidative changes like developmentof rancid odours and yellow discolouration than the muscle.Irradiation of skin samples under vacuum suppressed these changes.